Prognostic value of inflammatory response biomarkers using peripheral blood and [18F]-FDG PET/CT in advanced NSCLC patients treated with first-line chemo- or immunotherapy. (September 2021) - Seban, Romain-David; Assié, Jean-Baptiste; Giroux-Leprieur, Etienne; Massiani, Marie-Ange; Bonardel, Gérald; Chouaid, Christos; Deleval, Nicolas; Richard, Capucine; Mezquita, Laura; Girard, Nicolas; Champion, Laurence
Highlights: dNLR is a prognostic biomarker irrespective of the first-line systemic therapy. Features from lymphoid tissues on [18F]-FDG-PET/CT are also prognostic biomarkers. Spleen glucose metabolism (SLR) correlates with outcome after immunotherapy (IT). Bone marrow glucose metabolism (BLR) correlates with outcome after chemotherapy (CT). Patients with high dNLR and SLR have a major risk of progression on IT, but not on CT. Abstract: Objectives: We aimed to compare the prognostic value of inflammatory biomarkers extracted from pretreatment peripheral blood and [18F]-FDG PET for estimating outcomes in non-small cell lung cancer (NSCLC) patients treated with first-line immunotherapy (IT) or chemotherapy (CT). Materials and methods: In this retrospective multicenter study, we evaluated 111 patients with advanced NSCLC who underwent baseline [18F]-FDG PET/CT before IT or CT between 2016 and 2019. Several blood inflammatory indices were evaluated: derived neutrophil-to-lymphocyte ratio (dNLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP) and systemic immune-inflammation index (SII). FDG-PET inflammatory parameters were extracted from lymphoid tissues (BLR and SLR: bone marrow or spleen-to-Liver SUVmax ratios). Association with survival and relationships between parameters were evaluated using Cox prediction models and Spearman's correlation respectively. Results: Overall, 90 patients were included (IT:CT) (51:39pts). Median PFS was 8.6:6.6 months and median OS was not reached:21.2 months. In the IT cohort, high dNLR (>3), high SII (≥1, 270) and high SLR (0.77) were independent statistically significant prognostic factors for one-year progression-free survival (1y-PFS) and two-year overall survival (2y-OS) on multivariable analysis. In the CT cohort, high BLR (≥0.80) and high dNLR (>3) were associated with shorter 1y-PFS (HR 2.2, 95% CI 1.0–4.9) and 2y-OS (HR 3.4, 95CI 1.1–10.3) respectively, on multivariable analysis. Finally, BLR significantly but moderately correlated with most blood-based inflammatory indices (CRP, PLR and SII) while SLR was only associated with CRP (p < 0.01 for all). Conclusion: In advanced NSCLC patients undergoing first-line IT or CT, pretreatment blood and inflammatory factors evaluating the spleen or bone marrow on [18F]-FDG PET/CT provided prognostic information for 1y-PFS and 2y-OS. These biomarkers should be further evaluated for potential clinical application.